Managing organizational complexity : philosophy, theory and application - Richardson, Kurt A. (Managing the complex ;, 2005)
In introducing this first volume of a series exploring issues in managing complexity, Richardson (Institute for the Study of Coherence and Emergence) contends that no one has yet developed a reliable skill set for learning from the noise of complex systems.